Isokinetic assessment of knee joint muscles in shotokan karate kata athletes - Lisowska, A.; Murawa, M.; Ogurkowska, M. (Archives of Budo, 2020)
Background and Study Aim: Due to the observed phenomenon of knee joint pain in kata athletes, isokinetic assessment of hamstrings and quadriceps of shotokan karate kata athletes was performed and the results were compared to non-karate controls. The aim of the study was the question of whether under the influence of prolonged karate training there is an imbalance between the flexors and extensors of the knee joint and between the right and left lower limbs